Bridging the gaps between international and China’s domestic law on ship-sourced marine eco-environmental damage - Wang, Weikang; Sun, Yue; Xue, Guifang (Frontiers in Marine Science, 2025)
During the formulation of domestic legislation, States shall duly consider the obligations stipulated in the international treaties to which they are parties. This ensures the conformity of their municipal legal frameworks with international laws and regulations, and refrains from enacting domestic laws incompatible with treaty obligations. Notwithstanding this imperative, discrepancies persist between the provisions of China’s domestic legal regime regulating the scope of compensation for vessel-sourced oil pollution and the stipulations of pertinent international treaties and relevant state practices. Such legal inconsistencies may engender potential gaps in application, undermining the operational efficacy of international maritime regulatory instruments in this domain. To bridge such gaps, this paper synthesizes contemporary international maritime regulatory regime and comparative extraterritorial legislative precedents, endeavoring to from a coherent interpretative framework through which China’s domestic laws on oil pollution compensation scopes may achieve synergistic alignment, thereby securing uniformity in the rules and standards governing environmental obligations of States for marine ecological endangerment.